Educating the senses. The senses are not educated. (Journal of Parents and Teachers, 1997)
The article discusses the importance of the senses in the perception of the world and communication. It emphasizes the need to educate and refine the senses to improve sensitivity and understanding of reality. In addition, it mentions how sensory experiences influence our memory and emotions, enriching our interactions. Finally, it is emphasized that each person has a predominant sense that defines his or her way of relating to the environment.
Keywords: senses; perception; sensory experiences; sensibility